2014
DOI: 10.1111/jppi.12072
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Resilience for Parents of Children With Intellectual and Developmental Disabilities: A Review of Key Factors and Recommendations for Practitioners

Abstract: Parents of children with intellectual and/or developmental disabilities experience more stress in comparison to parents of normally developing children. Chronic stress could negatively influence parents' health while also impacting their ability to meet their child's needs. Despite this, there is a subset of parents who remain resilient in the face of significant stress in their lives. Knowledge of the factors that promote parental resilience could positively impact the services these families receive. The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
145
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(161 citation statements)
references
References 43 publications
7
145
1
8
Order By: Relevance
“…How stress is managed in the early stages of parenting, such as during the first 12 months, influences how parents view their child's disability, the coping strategies they develop and the way they provide ongoing care for their child (Karasavvidis et al . , Peer & Hillman ).…”
Section: Introductionmentioning
confidence: 99%
“…How stress is managed in the early stages of parenting, such as during the first 12 months, influences how parents view their child's disability, the coping strategies they develop and the way they provide ongoing care for their child (Karasavvidis et al . , Peer & Hillman ).…”
Section: Introductionmentioning
confidence: 99%
“…Parental physical and psychological well-being, parenting attitudes, parent-child interaction, marital functioning, and social relationships have all been implicated not only as at risk (Crnic, Arbona, Baker, & Blacher, 2009;Hauser-Cram, Warfield, Shonkoff, & Krauss, 2001) but also as potential moderators of risk when family functioning is strong and positive (Blacher, Baker, & Berkovits, 2013). Regardless, stress is one attribute that has consistently been implicated in the creation of risk for parents of children with ID (Peer & Hillman, 2014;Woodman et al, 2015) and may be the catalyst for many of the other risks that these families and children experience.…”
Section: Parent and Stress Processesmentioning
confidence: 99%
“…Diverging age and ability over time, violated developmental expectations, delayed developmental transitions, and continuing social stigma are among the issues that differentiate these children and their families. Although there is evidence in support of resilient functioning (Fenning & Baker, 2012;Peer & Hillman, 2014) and its connection to developmentally salient interventions (Guralnick, 2016), behavior disorders and more stressed parenting are two frequent consequences of ID. Both, however, have implications for child and parent well-being that are likely to be especially amenable to innovative intervention planning.…”
mentioning
confidence: 99%
“…Peer and Hillman () found evidence of a relationship between social support and parental stress management and resilience. Gallagher and Whiteley () reported that levels of social support were predictive of parental blood pressure and that parents of children with a developmental disability had higher systolic blood pressure than did parents without a child with a developmental disability.…”
Section: Resultsmentioning
confidence: 99%